A Co-loaded nitrogen-doped carbon nanotube electrocatalyst and its preparation method and application

The bimetallic Zn0.33Co0.67-MOF precursor prepared by hydrothermal method and the Co-supported nitrogen-doped carbon nanotube composite material prepared by calcining pyrolysis method solve the problem of uneven distribution of metal ions in the bimetallic MOFs-derived electrocatalyst, achieving efficient electrocatalytic oxygen and hydrogen evolution and excellent stability.

CN115896859BActive Publication Date: 2025-03-14SUZHOU UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310068373.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-06
Publication Date
2025-03-14
Estimated Expiration
2043-02-06

AI Technical Summary

Technical Problem

In existing bimetallic MOFs-derived electrocatalysts, the metal ions are unevenly distributed, resulting in uneven distribution of elements, insufficient active sites, and poor catalytic performance.

Method used

Bimetallic Zn0.33Co0.67-MOF precursor was prepared by hydrothermal method, and Co-supported nitrogen-doped carbon nanotube composite material was prepared by calcination pyrolysis method. The synergistic effect of zinc and the cobalt-based species were used to form a composite material with a high specific surface area and rich pore structure.

Benefits of technology

The conductivity and catalytic performance of the electrode material are improved, the overpotential of the HER and OER reactions are reduced, and the overpotential of the electrocatalytic oxygen and hydrogen evolution is achieved, and excellent stability is shown in the dual-electrode electrolytic cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896859B_ABST
    Figure CN115896859B_ABST
Patent Text Reader

Abstract

The present invention discloses a Co-loaded nitrogen-doped carbon nanotube electrocatalyst and a preparation method and application thereof. The preparation method comprises the following steps: (1) dispersing a cobalt salt, a zinc salt and a benzimidazole in a solvent, subjecting the solvent to a temperature rise and fall treatment, and obtaining a Zn 0.33 Co 0.67 ‑MOF precursor; (2) Zn 0.33 Co 0.67 The MOF precursor was calcined under an inert atmosphere to obtain Zn 0.33 Co 0.67 The Co-loaded nitrogen-doped carbon nanotube composite material prepared by the present invention has a high specific surface area and abundant active sites, and can be used for electrocatalytic hydrogen and oxygen evolution. Under low overpotential conditions, the current density in HER (147mV) and OER (281mV) reactions can reach 10mA cm ‑2 , showing excellent catalytic performance for hydrogen and oxygen evolution. 0.33 Co 0.67 The NCNT composite material can be used as both anode and cathode for overall water separation in a two-electrode electrolytic cell, requiring only a potential of 1.67 V to achieve 10 mA cm ‑2 The current density was 1.33 W and it showed excellent stability after 12 hours of continuous testing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalyst preparation, and in particular to a Co-loaded nitrogen-doped carbon nanotube electrocatalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen, as a renewable alternative fuel for environmental emissions, can generate electricity from sustainable energy sources such as wind and solar energy, and then achieve large-scale hydrogen production through water electrolysis. However, in the process of water electrolysis, HER and OER reactions involve multi-step electron transfer processes, each of which introduces a kinetic energy barrier, resulting in a large overpotential. High overpotentials often require higher voltages, which leads to very low electrolysis efficiency during water splitting. Therefore, there is an urgent need to design efficient and durable new electrocatalysts to overcome the high activation energy in the HER and OER processes to reduce the overpotential. At present, precious metal-based materials such as Pt, Ir, and Ru have been proven to have excellent catalytic properties, but their high cost and scarce natural reserves limit their large-scale use in the commercial field.

[0003] Metal-organic frameworks (MOFs) are coordination polymers self-assembled from multidentate organic ligands and transition metal ions. Due to their high specific surface area and abundant surface active centers, they are promising pyrolysis precursors and have been applied in various fields. In particular, metal / carbon composites obtained by pyrolysis of MOFs have been widely used in the field of electrocatalysis. The metals in these metal / carbon composites are wrapped by carbon shells, which can effectively prevent metal-based nanoparticles from being corroded by acidic or alkaline electrolytes. At the same time, the high conductivity of the carbon layer also contributes to the charge transfer between the electrolyte and the electrode during the electrocatalytic process. However, the catalytic performance of coordination polymers self-assembled from single metal ions and organic ligands is low. In order to improve the catalytic activity of MOFs-based catalysts, the electrocatalytic performance of MOFs-derived materials can be improved by doping heteroatoms and transition metal species. In recent years, more and more nitrogen-doped carbon-based composite materials have been transformed from single metal MOFs to bimetallic MOFs as sacrificial templates. Compared with single metal MOFs as precursors, bimetallic MOFs derived composite materials often show better electrocatalytic performance, which may be due to the favorable rearrangement of the electronic structure between the two metals, which reduces the kinetic energy barrier and promotes the HER and OER reactions. In addition, due to the presence of multiple valence states, unsaturated coordination and atomic defects, bimetallic MOFs compounds have abundant catalytic active centers, which can fully improve the electrocatalytic rate of their derived materials.

[0004] However, so far, most research groups have designed bimetallic MOFs with uneven metal ion distribution, which is not uniform. This can easily lead to uneven distribution of elements in their derived materials, resulting in too few exposed active sites and poor catalytic performance of the prepared electrode materials. For example, the Co / Ni bimetallic MOFs-derived carbon material designed by Wei's research group requires a potential of 1.59 V to achieve 10 mA cm -2 The current density of MOFs is 2.5 % (Wei et al., Int. J. Hydrogen Energy, 2020, 45(53): 28240-28251). Due to the lack of exploration of bimetallic MOFs-derived materials with other structures, how to selectively design bimetallic MOFs-derived materials with unique morphology and effectively improve the electrocatalytic performance of MOFs-derived materials is still an urgent problem to be solved in this field. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a Co-loaded nitrogen-doped carbon nanotube electrocatalyst and its preparation method and application. The present invention uses a hydrothermal method to form an ordered crystalline solid with metal ions and organic ligands through coordination bonds to obtain a bimetallic Zn 0.33 Co 0.67 -MOF precursor. During the subsequent calcination process, the pore-forming effect of zinc and the synergistic effect of zinc-based and cobalt-based species promoted the formation of a large number of carbon nanotubes under high-temperature pyrolysis conditions and exposed a large number of Co catalytic active sites. The combination of the two effectively improved the electrical conductivity and catalytic performance of the electrode material.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a method for preparing a Co-loaded nitrogen-doped carbon nanotube composite material, comprising the following steps:

[0008] (1) Dispersing cobalt salt, zinc salt and benzimidazole in a solvent, and subjecting the mixture to a temperature rise and fall treatment, to obtain Zn 0.33 Co 0.67 -MOF precursors;

[0009] (2) Zn 0.33 Co 0.67 -MOF precursor was calcined in an inert atmosphere to obtain Zn 0.33 Co 0.67 -NCNT composites.

[0010] Furthermore, in step (1), the cobalt salt is one or more of cobalt nitrate and its hydrates, and the zinc salt is one or more of zinc nitrate and its hydrates.

[0011] In some preferred embodiments, the cobalt salt is cobalt nitrate hexahydrate, and the zinc salt is zinc nitrate hexahydrate.

[0012] In some preferred embodiments, the molar ratio of the cobalt salt, the zinc salt and the benzimidazole is 2:1:3.

[0013] Furthermore, in step (1), the solvent is preferably a mixed solvent of N,N-dimethylformamide and water.

[0014] In some preferred embodiments, the solvent is a mixed solvent of N,N-dimethylformamide and water in a volume ratio of 1:1.

[0015] Furthermore, in step (1), the temperature rise and fall treatment is specifically as follows: heating to 135-150°C at a heating rate of 2-10°C / min, keeping the temperature for 36-60h, and then cooling to 20-30°C at a cooling rate of 2-10°C / h.

[0016] In some preferred embodiments, the temperature rise and fall treatment is specifically: heating to 140°C at a heating rate of 5°C / min, keeping the temperature for 48 hours, and then cooling to 25°C at a cooling rate of 5°C / h.

[0017] Furthermore, in step (1), the Zn 0.33 Co 0.67 -MOF precursor is a crystal belonging to the monoclinic system with a space group of C2 / c. Its asymmetric structural unit consists of a metal ion and two benzimidazole ligands. The metal ion is located on the C2 axis and coordinated by four benzimidazole ligands to form a tetrahedral coordination environment.

[0018] Furthermore, after the temperature rise and fall treatment in step (1), a light purple single crystal is precipitated, the mother liquor is filtered to collect the crystal, and the crystal is washed with anhydrous ethanol and dried to obtain the Zn 0.33 Co 0.67 -MOF precursors.

[0019] Furthermore, in step (2), the calcination treatment is specifically: heating to 950-1050° C. at a heating rate of 2-10° C. / min, keeping the temperature for 2-4 hours and then cooling naturally.

[0020] In some preferred embodiments, the calcination treatment is specifically: heating to 1000° C. at a heating rate of 5° C. / min, keeping the temperature for 3 hours and then cooling naturally.

[0021] The second aspect of the present invention provides a Co-loaded nitrogen-doped carbon nanotube composite material prepared by the preparation method described in the first aspect.

[0022] The third aspect of the present invention provides an application of the Co-loaded nitrogen-doped carbon nanotube composite material described in the second aspect in electrocatalyst.

[0023] Furthermore, the electrocatalyst is used for HER reaction, OER reaction or overall water splitting.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention prepares bimetallic Zn with a special crystal structure by hydrothermal method 0.33 Co 0.67 -MOF precursor, and then calcined and pyrolyzed to prepare Co-loaded nitrogen-doped carbon nanotube composites. The composite is rich in N-doped CNTs and multi-level pore structure, with a high specific surface area, which promotes the contact between the composite as a catalyst and the electrolyte, and is beneficial to improve the rapid transfer of charge and mass during the electrolysis process. In addition, Zn 0.33 Co 0.67 The large amount of pyridinic-N and graphitic-N in the -NCNT composite material brings abundant defective active sites to the carbon matrix, i.e., the active center in the electrocatalytic reaction process, which can improve the conductivity of the carbon matrix; and Zn 0.33 Co 0.67 -The Co particles on the surface of NCNT can form highly active Co-N species, which can provide more active sites for HER and OER reactions, thus playing a good catalytic role. In addition, carbon nanotubes have good electrical conductivity and corrosion resistance in acidic and alkaline environments. Combined with the strong skeleton structure composed of interconnected N-doped carbon nanotubes, the electrocatalytic activity and stability of the composite material are effectively improved.

[0026] 2. The Co-loaded nitrogen-doped carbon nanotube composite material provided by the present invention has a large specific surface area and a high metal ratio, and can be used as a catalyst for electrocatalytic oxygen and hydrogen evolution, and exhibits excellent catalytic performance for oxygen and hydrogen evolution. The composite material only needs a low overpotential of 147mV and 281mV to make the current density in HER and OER reactions reach 10mA cm -2 In addition, when Zn 0.33 Co 0.67 When the NCNT catalyst is used as both anode and cathode for overall water splitting in a two-electrode electrolytic cell, only a potential of 1.67 V is required to achieve 10 mA cm -2 Moreover, after 12 hours of continuous testing, its stability is excellent. 0.33 Co 0.67 Zn obtained by calcination of MOF crystals 0.33 Co 0.67-NCNT can be used as an electrocatalytic material in electrocatalytic hydrogen and oxygen evolution. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Zn 0.33 Co 0.67 -MOF crystal structure: (a) Zn II The coordination environment of the ion and the bridging mode of Bim; (b) is a two-dimensional (4,4) layer based on two one-dimensional chains; (c) is a two-dimensional layer of AB stacking along the a-axis; (d) is a two-dimensional layer crossed along the c-axis;

[0028] Figure 2 Zn 0.33 Co 0.67 - X-ray powder diffraction pattern of MOF crystals;

[0029] Figure 3 Zn 0.33 Co 0.67 -X-ray powder diffraction pattern of NCNT composites;

[0030] Figure 4 Zn 0.33 Co 0.67 -High-resolution transmission electron microscopy images of NCNT composites (ac) and diffraction rings of area electron diffraction (d);

[0031] Figure 5 Zn 0.33 Co 0.67 -X-ray photoelectron spectroscopy analysis spectrum (a), Co 2p spectrum (b), C 1s spectrum (c) and N1s spectrum (d) of NCNT composite materials;

[0032] Figure 6 Zn 0.33 Co 0.67 -Field emission electron scanning image of MOF crystal (a), Zn 0.33 Co 0.67 -Field emission electron scanning images of NCNT composite materials (bc), Zn 0.33 Co 0.67 -NCNT composite pore size distribution (d), Zn 0.33 Co 0.67 -NCNT composites carbon nanotube diameter distribution (e) and Zn 0.33 Co 0.67 -Mapping diagram of C, Co and N elements in NCNT composite materials (f);

[0033] Figure 7 Zn 0.33 Co0.67 -N2 adsorption-desorption isotherms (a) and pore size distribution curves (b) of NCNT-1000, Co@CNT-1000 and PC-1000 materials;

[0034] Figure 8 20% Pt / C, PC-1000, Co@CNT-1000 and Zn 0.33 Co 0.67 -HER linear sweep voltammetry curve (a), Tafel slope (b), and OER linear sweep voltammetry curve (c), Tafel slope (d) of NCNT-1000 catalyst;

[0035] Fig. 9 Zn 0.33 Co 0.67 -NCNT-1000 (a), Co@CNT-1000 (b), and PC-1000 (c) for OER reaction in the non-Faraday voltage range (1.05-1.35 V vs. RHE) at different scan rates (10-100 mV s -1 ) Cyclic voltammetry curves of the test; Linear relationship between the current density difference ΔJ and the scan rate of the corresponding CV curves of different catalysts at a voltage of 1.2 V vs. RHE (d);

[0036] Fig.10 Zn 0.33 Co 0.67 -Linear sweep voltammetry curves of NCNT-1000 in dual-electrode integrated water splitting (a) and linear sweep voltammetry curves before and after 12 h of cycling (b). The inset in (b) shows the current density of 10 mA cm within 12 h of cycling. -2 The corresponding voltage value changes with time. DETAILED DESCRIPTION

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0038] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0039] Example 1

[0040] This embodiment relates to the preparation of a Co-loaded nitrogen-doped carbon nanotube composite material, and the specific operations are as follows:

[0041] (1) Zn 0.33 Co 0.67 -Synthesis of MOF crystals

[0042] 1.33 mmol of Co(NO3)2·6H2O, 0.67 mmol of Zn(NO3)2·6H2O and 2 mmol of benzimidazole were added to 15 mL of a mixed solvent (DMF and H2O were mixed in a volume ratio of 1:1). After sufficient stirring, the resulting suspension was transferred to a polytetrafluoroethylene autoclave and heated in a programmed temperature-controlled oven at 5 °C min -1 Heat to 140℃, keep constant temperature for 2 days, then heat at 5℃ h -1 After slowly cooling to room temperature at a speed of , collect light purple square single crystals. After filtering the mother liquor, wash the crystals several times with anhydrous ethanol, and place them in the air to dry naturally for 3 hours to enrich the sample. Finally, dry the powder at 80℃.

[0043] The prepared crystals were characterized by single crystal X-ray diffraction. The results showed that Zn 0.33 Co 0.67 -MOF crystal is monoclinic, space group is C2 / c. Its crystal structure is shown in the figure Figure 1 As shown, Zn 0.33 Co 0.67 The asymmetric structural unit of -MOF is composed of a metal ion and two benzimidazole ligands (bim). The metal ion is located on the C2 axis and coordinated by four bim ligands to form a tetrahedral coordination environment (1(a)). The lengths of the MN (M is Co or Zn) bonds are almost the same, 1.968 and All of them are consistent with the typical values ​​of ZIF. In addition, the bond angles around the metal ion center are 103.4°, 106.7° and 118.9°. The deprotonated imidazole ring acts as a V-shaped ligand, connecting the two metal centers singly. Interestingly, all bim molecules are divided into two groups, and each group of bim ligands is packed in a sliding manner, connecting the metal ions into a 1D chain [M(bim)] ∞ If the bim ligand is regarded as a linker, there are two 1D chains with an intersection angle of 90°, which are intertwined to form a 2D (4,4) layer [M(bim)2] ∞ ( Figure 1 (b)). Figure 1 (c) It can be seen that all metal ions in a layer are absolutely coplanar. In addition, these two-dimensional layers are stacked in an AB type, with the metal ions in one layer located below the grid of the adjacent layer along the c-axis ( Figure 1 (d)).

[0044] Then, Zn 0.33 Co 0.67 -MOF crystals were subjected to X-ray powder diffraction test, and the test results were as follows Figure 2 As shown, the diffraction peaks obtained by the powder diffraction test are completely consistent with the simulated diffraction peaks. Therefore, it can be seen that the above preparation method is used to prepare Figure 1 The crystals have the crystal structure shown, and the obtained samples have high purity.

[0045] (2) Composite material Zn 0.33 Co 0.67 Preparation of -NCNT

[0046] The synthesized Zn 0.33 Co 0.67 The MOF precursor sample was transferred to a corundum ark, which was then transferred to a temperature-controlled tube furnace and placed horizontally in the center of the tube furnace. -1 The temperature was raised to 1000°C and calcined for 3 hours. After the tube furnace was cooled naturally, a black powder substance Zn was obtained. 0.33 Co 0.67 -NCNT composites, named Zn 0.33 Co 0.67 -NCNT-1000.

[0047] The black powder material prepared above was subjected to an X-ray powder diffraction test, and the test results were as follows: Figure 3 As shown in the figure, sharp diffraction peaks can be observed at 2θ of 44.32°, 51.61° and 75.95°, which correspond to the (111), (200) and (220) crystal planes of hexagonal metal Co (JCPDF No.15-0802), respectively. In addition, a diffraction peak is observed at about 2θ of 25.69°, which is related to the (002) crystal plane diffraction of graphite carbon, which also indicates that the carbon matrix is ​​highly graphitized.

[0048] High-resolution transmission electron microscopy (HRTEM) was then used to characterize the Zn 0.33 Co 0.67 -NCNT-1000 composite material was characterized, and the results are as follows Figure 4 As shown in (a)-4(c), Zn 0.33 Co 0.67 -NCNT Co's (200) and (111) crystal planes coincide with the lattice fringes of 0.184nm and 0.205nm, respectively. In addition, the (200) crystal plane of Co-N and the (002) crystal plane of C can also find corresponding lattice fringes, which are 0.213nm and 0.314nm, respectively. And the selected area electron diffraction (SAED) ( Figure 4The diffraction rings in (d)) and Zn 0.33 Co 0.67 -All diffraction rings of NCNT-1000 are consistent, which indicates that the obtained material has good crystallinity.

[0049] In addition, X-ray photoelectron spectroscopy (XPS) was used to study the surface elemental composition and chemical phase of the samples. Figure 5 As shown in (a), the peaks corresponding to Co, O, N and C can be observed in the full XPS spectrum of the black powder sample, among which the signal of O species may come from physically adsorbed oxygen. The types of different elements were studied by high-resolution spectroscopy. Figure 5 (b) is the Co 2p spectrum, where 780.17 eV (Co 2p 3 / 2 ) and 796.35 eV (Co 2p 1 / 2 ) can be attributed to Co 3+ , while 785.52eV and 802.80eV are two satellite peaks (noted as "Sat."), while the peaks at 777.34eV and 792.96eV point to metal Co, and the peak at 797.02eV is equivalent to Co 2+ In addition to the above peaks, Zn 0.33 Co 0.67 -NCNT also has a peak around 782.51eV, which can be attributed to Co combined with nitrogen, indicating that Zn 0.33 Co 0.67 The Co-N bond exists in the NCNT sample, which is an effective active site in the electrocatalytic process. Figure 5 (c) is the high-resolution spectrum of C1s, which consists of four peaks, namely CC (284.56 eV), CO (285.73 eV), CN / C=N (287.84 eV) and OC=O (294.40 eV). Figure 5 (d) It can be seen that there are three types of nitrogen in the sample, including NO (404.31 eV), graphite-N (402.18 eV), pyrrole-N (400.74 eV), Co-N (99.59 eV) and pyridine-N (398.27 eV) in the N 1s spectrum. The presence of pyrrole-N and pyridine-N functional groups can also be related to the presence of H in the electrolyte. + interaction to enhance the electrocatalytic activity and thus promote the efficiency of the hydrogen evolution reaction.

[0050] Observation of Zn by Field Emission Electron Scanning 0.33 Co 0.67 -MOF crystals and the morphology of the composites prepared after calcination, by Figure 6 (a) It can be seen that Zn 0.33 Co 0.67-MOF crystals have a smooth surface and uniform size distribution. After calcination at 1000℃, the derived Zn 0.33 Co 0.67 -NCNT-1000 basically retains the original shape of the parent MOFs, except that the cubic structure is slightly collapsed (6(b)), and some regularly arranged pores appear on the surface of the matrix with an average diameter of 33.72±8.33nm ( Figure 6 (c), 6(d)). To explore the origin of the pores, Zn 0.33 Co 0.67 -NCNT-1000 was slightly ground, and it was found that a large number of CNTs were produced in the composite material, and highly dispersed Co particles were embedded in the carbon matrix. The average diameter of these CNTs was 34.29±8.31nm ( Figure 6 (e)), with Zn 0.33 Co 0.67 -NCNT surface pore size is basically the same. 0.33 Co 0.67 -The pores on the surface of NCNT-1000 come from CNTs. This is mainly due to Zn 0.33 Co 0.67 -The Co metal sites on the MOF surface can catalyze graphitization during pyrolysis, thereby converting Zn 0.33 Co 0.67 -The ligands in MOF decompose to form CNTs.

[0051] In addition, through the element mapping diagram ( Figure 6 (f)) It can be seen that the three elements C, N, and Co are evenly dispersed in the Zn 0.33 Co 0.67 -NCNT-1000 composite material.

[0052] The present invention also uses nitrogen low temperature adsorption technology to Zn 0.33 Co 0.67 -The porous characteristics and specific surface area of ​​NCNT-1000 materials were evaluated, and Zn 0.33 Co 0.67 -N2 adsorption-desorption isotherms and pore size distribution curves of NCNT-1000, Co@CNT-1000 and PC-1000 materials Figure 7 shown. Figure 7 (a) N2 adsorption-desorption isotherms of different materials, among which Zn 0.33 Co 0.67-NCNT-1000's N2 adsorption-desorption isotherm is type IV adsorption in the IUPAC classification. Another obvious feature is that there is an H2-type hysteresis loop between P / P0 of 0.45-1.0, which indicates that mesopores and macropores coexist in the composite material. Zn 0.33 Co 0.67 -NCNT-1000 has a specific surface area of ​​286.2508m 2 g -1 , the total volume is 0.1918cm 3 g -1 This also shows that the composite material has a higher specific surface area and a larger porosity, which is beneficial to improving the electrocatalytic performance of the material. The corresponding pore size distribution diagram is shown in Figure 7 As shown in (b), it can be seen from the figure that Zn 0.33 Co 0.67 -NCN-1000T has a wide pore size distribution range (2.1-90nm), mainly concentrated in 3nm and 15nm, showing obvious multi-level pore characteristics. The multi-level pore structure can promote charge and mass transfer in the electrocatalytic process, making it easier for reactants to contact exposed active sites and improving the conductivity of the material.

[0053] Comparative Example 1

[0054] Preparation of PC-1000: 1.0 mmol of Zn(NO3)2·6H2O and 2 mmol of benzimidazole were added to 15 mL of a mixed solvent (DMF and H2O were mixed in a volume ratio of 1:1). After sufficient stirring, the resulting suspension was transferred to a polytetrafluoroethylene autoclave and heated in a programmable temperature-controlled oven at 5 °C min -1 Heat to 140℃, keep constant temperature for 2 days, then heat at 5℃ h -1 After slowly cooling to room temperature at a speed of 100 °C, the solid was collected, washed and dried to obtain Zn-MOFs. The dried Zn-MOFs sample was transferred to an ark, placed horizontally in the center of a tube furnace, and heated at 5 °C min under the protection of N2 gas flow. -1 The temperature was raised to 1000°C at a rate of 1000°C and the calcination was continued for 3 hours. After the tube furnace was cooled naturally, the black powder was collected and named PC-1000.

[0055] Comparative Example 2

[0056] Preparation of Co@CNT-1000: 1.0 mmol of Co(NO3)2·6H2O and 2 mmol of benzimidazole were added to 15 mL of a mixed solvent (DMF and H2O were mixed in a volume ratio of 1:1). After sufficient stirring, the resulting suspension was transferred to a polytetrafluoroethylene autoclave and heated in a programmed temperature-controlled oven at 5 °C min -1 Heat to 140℃, keep constant temperature for 2 days, then heat at 5℃ h-1 After slowly cooling to room temperature at a speed of 100 °C, the solid was collected, washed and dried to obtain Co-MOFs. The dried Co-MOFs sample was transferred to an ark, placed horizontally in the center of a tube furnace, and heated at 5 °C min under the protection of N2 gas flow. -1 The heating rates were respectively heated to 81000℃ and calcined for 3 hours. After the tubular furnace was naturally cooled, the black powder was collected and named Co@CNT-1000.

[0057] Electrocatalytic Applications

[0058] (1) Zn 0.33 Co 0.67 -Electrocatalytic performance of NCNT-1000 catalyst in HER and OER reactions

[0059] Zn 0.33 Co 0.67 -The electrocatalytic performance test of NCNT-1000 catalyst was carried out using a three-electrode system at room temperature using a Shanghai Chenhua electrochemical workstation. The specific operation is as follows:

[0060] Preparation of working electrode: 5 mg of Zn 0.33 Co 0.67 -NCNT-1000 was dispersed in 1 mL of a 1:9 v / v (Nafion: CH3CH2OH) mixture and ultrasonicated for at least 30 minutes to form a uniform black slurry. Then 5 μL of the black slurry was dropped on a glassy carbon electrode (GCE, diameter: 3.0 mm) and dried naturally at room temperature to form a working electrode.

[0061] A platinum sheet was used as a counter electrode and a Hg / HgO electrode was used as a reference electrode, which were installed with the working electrode prepared above. A KOH aqueous solution with a concentration of 1 mol / L was used as an electrolyte.

[0062] The catalytic activity was tested by linear cyclic voltammetry in 1 M KOH solution at 5 mV s -1 The catalytic activity of the sample was recorded at a scan rate of 50 mVs before the formal measurement of linear sweep voltammetry (LSV). -1 The catalyst was activated at a scan rate of 1.5 % and cyclic voltammetry (CV) was performed at least 20 times to stabilize the current. The Tafel curve can be obtained from 5 mV s -1 The LSV curve is obtained at a scanning speed of .

[0063] The catalytic stability was evaluated by chronoamperometry and CV with a scan rate of 50 mV s -1 , for 1000 cycles. CV can be used to calculate the double layer capacitance (C dl) and the estimated electrochemically active surface area (ECAS). The CV tests were performed in the non-Faraday potential range of 1.05-1.35 V and 0.6-0.9 V (vs. RHE) at different scan rates (10-100 mV s -1 ) is carried out.

[0064] Electrochemical impedance spectroscopy (EIS) measurements were performed in 1 M KOH (pH = 14) solution from 105 to 0.01 Hz with an AC amplitude of 0.005 V.

[0065] All the above tests are based on the Hg / Hg2Cl2 electrode as a reference, and all potentials vs. SCE in the present invention are converted to reversible hydrogen electrode according to the following formula:

[0066] E(RHE)=E(SCE)+0.242+0.059pH

[0067] Figure 8 (a) 20% Pt / C, PC-1000, Co@CNT-1000 and Zn 0.33 Co 0.67 -NCNT-1000 catalyst HER linear sweep voltammetry curve, as shown in the figure, Zn 0.33 Co 0.67 -NCNT-1000 showed good HER response, namely Zn 0.33 Co 0.67 -NCNT-1000 at 10mA cm -2 The overpotential is 147 mV, which is only 93 mV higher than the commercial 20% Pt / C catalyst. The Tafel slope is often used to study the kinetics of OER and HER, that is, the degree to which the electrode potential needs to change to achieve a certain current. Figure 8 (b) It can be seen that Zn 0.33 Co 0.67 - The Tafel slope of NCNT-1000 is only 83.3mV dec -1 , and its Tafel slope value indicates that it follows the Volmer-Heyrovesky mechanism in the HER process. 0.33 Co 0.67 -NCNT-1000 also exhibits good performance in OER reactions, such as Figure 8 As shown in (c), Zn 0.33 Co 0.67 -NCNT-1000 at a current density of 10 mA cm -2 When the overpotential is only 281 mV, the Tafel slope in OER is 52.0 mV dec. -1 , showing excellent reaction rate.

[0068] The electrochemically active surface area (ECSA) and double layer capacitance (C dl ) is proportional to C dl Reflects ECSA. Fig. 9 (a)-9(c) are catalysts Zn 0.33 Co 0.67 -NCNT-1000, Co@CNT-1000 and PC-1000 were selected in 1 M KOH electrolyte within the non-Faraday voltage range (1.05-1.35 V vs. RHE) where the OER reaction occurs at different scan rates (10-100 mV s -1 ) cyclic voltammetry curves. Calculate the current density difference ΔJ (J = ja-jc) corresponding to the CV curve when the voltage is 1.2 V vs. RHE, and draw a linear relationship between ΔJ and scan rate ( Fig. 9 (d)), where Zn 0.33 Co 0.67 -NCNT-1000 C dl The highest value is 24.47mF cm -2 . It can be seen from this that Zn 0.33 Co 0.67 -NCNT-1000 catalyst has the largest active surface area, which is due to its unique multi-level pores and a large number of exposed electrochemically active centers.

[0069] (2) Zn 0.33 Co 0.67 - Overall water splitting performance test of NCNT-1000 catalyst

[0070] The present invention uses a dual-electrode device to evaluate Zn 0.33 Co 0.67 -NCNT-1000 catalyst overall water splitting performance in 1 M KOH. The specific operation is as follows: in 1 M KOH solution, two clean carbon cloths were used as carriers (catalyst loading was 1 mg cm -2 ), measuring overall water splitting in a two-electrode cell.

[0071] Depend on Fig.10 As shown in (a), Zn 0.33 Co 0.67 -NCNT-1000 catalyst at a current density of 10 mA cm -2 The voltage is only 1.67 V, showing excellent overall water splitting performance. Fig.10 (b) is the LSV curve before and after 12h of cycling. It can be seen from the figure that there is no significant deviation in the LSV curve before and after the cycle. 0.33 Co 0.67-NCNT-1000 has good stability in 1M KOH electrolyte and can work effectively for a long time.

[0072] By preparing Zn 0.33 Co 0.67 -NCNT catalysts were used in electrocatalytic hydrogen and oxygen evolution reactions and overall water decomposition experiments. It was found that Zn 0.33 Co 0.67 -NCNT catalysts exhibit high catalytic activity in both HER and OER reactions, and can achieve high current density at low overpotentials; and can be used as both anode and cathode in the overall water separation of a dual-electrode electrolytic cell, exhibiting high catalytic activity and excellent stability. 0.33 Co 0.67 -NCNT composites can be used as bifunctional electrocatalysts for electrocatalytic hydrogen and oxygen evolution.

[0073] The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing a Co-loaded nitrogen-doped carbon nanotube composite material, characterized in that: The following steps are involved: (1) Disperse cobalt salt, zinc salt and benzimidazole in a solvent and, after heating and cooling, obtain Zn 0.33 Co 0.67 -MOF precursor; the solvent is a mixed solvent of N, N-dimethylformamide and water in a volume ratio of 1:1; The Zn 0.33 Co 0.67 -MOF precursor is crystalline, belongs to the monoclinic system, and the space group is C 2 / c Its asymmetric structural unit consists of a metal ion and two benzimidazole ligands. The metal ion is located at C 2 axis and coordinated by four benzimidazole ligands to form a tetrahedral coordination environment; (2) Zn 0.33 Co 0.67 -MOF precursor was calcined in an inert atmosphere to obtain Zn 0.33 Co 0.67 -NCNT composites.

2. The preparation method according to claim 1, characterized in that: In step (1), the cobalt salt is one or more of cobalt nitrate and its hydrates, and the zinc salt is one or more of zinc nitrate and its hydrates.

3. The preparation method according to claim 1, characterized in that: In step (1), the temperature rise and fall treatment is specifically as follows: heating to 135-150°C at a heating rate of 2-10°C / min, keeping the temperature for 36-60 hours, and then cooling to 20-30°C at a cooling rate of 2-10°C / h.

4. The preparation method according to claim 3, characterized in that: The temperature rise and fall treatment is specifically as follows: heating to 140°C at a heating rate of 5°C / min, keeping the temperature for 48 hours, and then cooling to 25°C at a cooling rate of 5°C / h.

5. The preparation method according to claim 1, characterized in that: In step (2), the calcination treatment is specifically: heating to 950-1050°C at a heating rate of 2-10°C / min, keeping the temperature for 2-4 hours and then cooling naturally.

6. The preparation method according to claim 5, characterized in that: The calcination treatment is specifically as follows: heating to 1000°C at a heating rate of 5°C / min, keeping the temperature for 3 hours and then cooling naturally.

7. A Co-loaded nitrogen-doped carbon nanotube composite material prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the Co-loaded nitrogen-doped carbon nanotube composite material according to claim 7 in electrocatalysts, characterized in that: The electrocatalyst is used for HER reaction, OER reaction or overall water splitting.

Citation Information

Patent Citations

  • Nitrogen-doped carbon material with dual functional oxygen catalysis performance and rich in CNTs and Co particles and preparation method and application of nitrogen-doped carbon material

    CN107597162A